COMPUTATIONAL TECHNIQUE FOR MODELING AND CLUSTERING OF FEEDBACK CONTROL IN GALAXIES USING GRAVITATIONAL THERMODYNAMICS - GSR, EMIL SELVAN; N, GAYATHRI; Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
A model for clustering of galaxies through relativistic gravitational thermodynamics is laid on. Unlike the theories presented which consists of point mass system in expanding universe we presented the methodology in which partial differential equation & thermodynamic equations with the equation of state in accord with gravitational interaction between particles in order to study extended structures of universe. Â Â